The Effect of Cities and Ports on Economic Growth in Indonesia : The Mediating Role of Containerization - Pasaribu, Dominggo; Nasution, Zulkifli; Lubis, Satia Negara; Absah, Yeni (Journal of Ecohumanism, 2024)
Containerization, Containerization, a developing method for transporting goods, is revolutionizing thetransportation system and industry on a global scale. This study examines the effect of containerization on economic growth and its role in mediating the impact of cities and ports on economic development in Indonesia. The study, which employed a quantitative descriptive approach, collected panel data from 50 cities and ports involved in container loading and unloading activities in Indonesia and analyzed the data using Structural Equation Modeling (PLS-SEM). The research findings demonstrate that containerization has a positive and significant effect on economic growth and mediates the impact of cities and ports on economic development in Indonesia. These results provide an empirical basis for formulating policies and developing more effective economic strategies for archipelagic countries based on interrelated variables. Investment in thoughtful infrastructure and collaborative and comprehensive stakeholder strategies can provide substantial economic benefits for sustainable development goals (SDGs), contributing to the global impact of containerization.